FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERUBAHAN KONTRAK LUMP SUM PRICE MENJADI UNIT RICE (Jurnal Spesialis Teknik Sipil (JSpTS), 2019)
The work contract for the Surabaya-Gempol toll road relocation project Porong-Gempolpackage 2 Porong-Kejapanan has been signed, namely in the form of a lump sum contract.Due to a request from BPJT to change the design from 2 x 4 lanes to 2 x 6 lanes on theSurabaya-Gempol toll road relocation project, Porong-Gempol 2 Porong-Kejapanan, thecontractor intends to propose a contract change from a lump sum to a unit price contract.This study aims to determine and determine the factors that influence changes in the contract.It turns out that by distributing questionnaires, it can be found that there are five mainvariables, namely service users (X1), service providers (X2), third parties (X3), contracts (X4)and environment (X5) that affect the final outcome of contract change (Y). By using factoranalysis and stepwise regression analysis aided by the SPSS program, it was found that onlythe service user variable (X1) and the service provider variable (X2), which significantlyaffected the contract change dependent variable (Y). And that influence is expressed by therelationship Y = -1,171 + 0,268 X1 + 0,529 X2.Keywords: lump sum contract, unit price contract,Â  factor analysis, multiple regressionanalysis